Lipodystrophy in Ecuador: A Critical Review of Its Low Visibility and Challenges in Differentiating It from Obesity in Clinical Practice - Sofía D. Véliz; Daliannis Rodríguez; Mario A. García (PT. Riset Press International, 2026)
The present systematic review of Ecuadorian academic literature (2015-2025) establishes that lipodystrophy is a nosological entity characterized by high clinical prevalence but low epidemiological visibility, with research predominantly concentrated on the therapeutic sequelae of diabetes mellitus and HIV/AIDS (SLAV). Evidence reveals that the condition's chronic underreporting is perpetuated by the diagnostic differentiation challenge, in which manifestations of lipoaccumulation (lipo-hypertrophy due to insulin or visceral fat due to HAART) are systematically subsumed under the umbrella of obesity in general clinical practice. This confusion hinders the identification of specific etiological factors and minimizes the recognition of the high metabolic and cardiovascular risks associated with these pathological adipose alterations. It is concluded that the imperative is to establish standardized national clinical protocols that mandate rigorous differential diagnosis for obesity, thereby reducing underreporting and ensuring specialized therapeutic intervention in Ecuador.